Knowledge management, decision-making style and organizational performance - Abubakar Mohammed Abubakar; Hamzah Elrehail; Maher Ahmad Alatailat; Alev Elçi (Journal of Innovation & Knowledge (JIK), 2019)
A synthesis of existing Industry 4.0 literature depicts that knowledge management and decision making strategies are crucial factors for organizations. This article highlights the need and develops a framework for knowledge management and decision-making style by reviewing existing management literature. This research proposes a framework that supports the relationship between knowledge management enabling factors (i.e., organizational member's collaboration, T-shaped skills, learning and IT-support) and organizational performance, and the mediating effect of knowledge creation process. The article also propose that decision-making style (i.e., intuitive and/or rational) will moderate the relationship between knowledge creation process and organizational performance. A set of propositions that represent an empirically-driven research agenda, and also describe the relationships between the focal variables are presented to enhance audience's understanding within a business context.
Keywords: O31; L2; M12; 650; Intuitive decision-making; Knowledge creation; Knowledge management; Organizational performance; Rational decision-making